The third space, student and staff co-creation of gamified informal learning: an emerging model of co-design (UCL Press, 2024)
This article draws from the authors' exploration of an innovative third space approach to engaging students with informal learning through the use of co-design and co-creation, which sits outside traditional subject delivery spaces. The third space project, the Digital Citizenship Programme, centres on the transformative experience and dialogic encounter for participants. The third space in this context was constituted by co-design and co-production involving students, alumni, academics and professional service staff. The project evaluated third space activity in terms of co-design, through its development process and in what is achieved by participants' engagement with it. The aims were to analyse the mutuality and relational aspects of the innovative pedagogic intervention; the development of transferable skills and agentic development in the third space; and the dialogic experience for participants. The research data were collected over a period of three years, using focus groups, co-creation workshop observations and field notes. This project builds on the body of research that focuses on partnerships with students that fall under the umbrella of the third space. The article underlines the importance of co-creation approaches in building the relational and dialogic dynamic in higher education spaces.